La agenda ausente de las entrevistas a fondo y una tipología de calidad del cuestionario político - Štambuk Mayorga, Patricia (Estudios sobre el Mensaje Periodístico, 2002)
A content analysis of interpretative interviews published in the main written media of Chile before and after a presidential election reveals their marked preferences to both sources and topics. Politicians as well as politics dominate the journalistic menu; however, the so-called “real topics” or “people’s topic” are, at the same time, the absent agenda. This article provides data about this unsatisfactory mediation of the press; it also warns about the uniformity in the organization of the texts; and it proposes a methodology to examine the quality and tendencies in the political questionnaire based on a typology of the questions of journalists.
Keywords: In- depth interviews; sources; topics; questionnaires; mass media